2007
DOI: 10.1128/iai.01470-06
|View full text |Cite
|
Sign up to set email alerts
|

Possible Correlates of Long-Term Protection againstHelicobacter pylorifollowing Systemic or Combinations of Mucosal and Systemic Immunizations

Abstract: The ability to induce long-term immunity to Helicobacter pylori is necessary for an effective vaccine. This study was designed to establish the most efficient route(s) (systemic, mucosal, or a combination) of immunization for induction of long-term immunity and to define correlates of protection. Mice were immunized orally alone (oral group), intramuscularly (i.m.) alone (i.m. group), orally followed by i.m. (oral/i.m. group), or i.m. followed by orally (i.m./oral group). Long-term protective immunity to oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Although LT or CT and their mutants have been extensively used as mucosal adjuvants, their use as systemic adjuvants has been far more limited. CT has been shown as an effective systemic adjuvant in several studies (16,26,48,53,58). Interestingly, it was shown that, whereas the systemic administration of CT induced both TH1-and TH2-type responses, the nontoxic moiety of CT, CTB, induced TH1-type responses (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LT or CT and their mutants have been extensively used as mucosal adjuvants, their use as systemic adjuvants has been far more limited. CT has been shown as an effective systemic adjuvant in several studies (16,26,48,53,58). Interestingly, it was shown that, whereas the systemic administration of CT induced both TH1-and TH2-type responses, the nontoxic moiety of CT, CTB, induced TH1-type responses (2).…”
Section: Discussionmentioning
confidence: 99%
“…CT has been shown as an effective systemic adjuvant in several studies (16,26,48,53,58). If combinations of mucosal and systemic vaccinations should be used for humans, it would be more practical to use the same vaccine formulation for both mucosal and systemic vaccination regimens.…”
mentioning
confidence: 99%
“…It has been reported that intramuscular immunization is most effective and produces the most longlasting effects against infection with respect to the induction of anti-H. pylori-specific antibodies [54]. Since the protective effect correlated with increased IL-12 production in splenocytes, systemic activation of Th1 responses may be required to increase the duration of protection from immunization.…”
Section: Vaccines For Helicobacter Pylori Infectionmentioning
confidence: 99%
“…The expression level of B7-H1 in H. pylori infected gastric epithelium is much higher than that of uninfected cells. B7-H1 was identified as a programmed death-ligand 1, PDL-1 belonging to the B7 family of molecules [26][27][28]. PDL-1 binds to the programmed death-1 (PD-1) receptor, which results in the down-regulation of T cell activation [29].…”
Section: Antigen Presenting Cellsmentioning
confidence: 99%
“…Since H. pylori colonization occurs at the mucosal level, particular emphasis has been given to oral immunization, although other mucosal routes of immunization [36], as well as the parenteral route [35] or prime-boost regimens, have been considered [37][38][39]. Mucosal immunization requires the use of strong mucosal adjuvants, as proteins are poor immunogens when administered mucosally.…”
Section: Vaccination Against H Pylori In Animal Modelsmentioning
confidence: 99%